2010
DOI: 10.2337/db09-0287
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory CD11c+CD206+ Adipose Tissue Macrophages Are Associated With Insulin Resistance in Human Obesity

Abstract: OBJECTIVEInsulin resistance and other features of the metabolic syndrome have been causally linked to adipose tissue macrophages (ATMs) in mice with diet-induced obesity. We aimed to characterize macrophage phenotype and function in human subcutaneous and omental adipose tissue in relation to insulin resistance in obesity.RESEARCH DESIGN AND METHODSAdipose tissue was obtained from lean and obese women undergoing bariatric surgery. Metabolic markers were measured in fasting serum and ATMs characterized by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
522
4
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(575 citation statements)
references
References 53 publications
(77 reference statements)
42
522
4
7
Order By: Relevance
“…While well-established in mice [34,35], the existence of distinct M1 and M2 subsets of adipose tissue macrophages has not been confirmed in human, where macrophages have rather been described as being a mix between M1 and M2 phenotypes [36]. In addition to adipose tissue macrophages infiltration, obesity causes a phenotypic switch from the M2 to M1 phenotype, correlating with insulin resistance both in mice and humans [34][35][36]. Direct and paracrine signals issued from M1 macrophages can impair insulin signaling and adipogenesis in adipocytes whereas M2 macrophages seem to protect against obesity-induced insulin resistance [4].…”
Section: Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…While well-established in mice [34,35], the existence of distinct M1 and M2 subsets of adipose tissue macrophages has not been confirmed in human, where macrophages have rather been described as being a mix between M1 and M2 phenotypes [36]. In addition to adipose tissue macrophages infiltration, obesity causes a phenotypic switch from the M2 to M1 phenotype, correlating with insulin resistance both in mice and humans [34][35][36]. Direct and paracrine signals issued from M1 macrophages can impair insulin signaling and adipogenesis in adipocytes whereas M2 macrophages seem to protect against obesity-induced insulin resistance [4].…”
Section: Adipose Tissuementioning
confidence: 99%
“…M a n u s c r i p t 6 Macrophages can be classified into two distinct subtypes: the "classically activated macrophages" phenotype, termed M1, which secrete pro-inflammatory cytokines such as IL-1β, IL-6, TNF-α, and the "alternatively activated macrophages" phenotype, termed M2 which produce anti-inflammatory cytokines such as IL-10 [4]. While well-established in mice [34,35], the existence of distinct M1 and M2 subsets of adipose tissue macrophages has not been confirmed in human, where macrophages have rather been described as being a mix between M1 and M2 phenotypes [36]. In addition to adipose tissue macrophages infiltration, obesity causes a phenotypic switch from the M2 to M1 phenotype, correlating with insulin resistance both in mice and humans [34][35][36].…”
Section: Adipose Tissuementioning
confidence: 99%
“…These macrophages surround and engulf elements of apoptotic adipocytes and consequently contain high quantities of intracellular fat. 72,73 During pregnancy, serum markers of inflammation are raised in overweight and obese women. 74 Placental tissue examined postpartum from obese mothers also has a higher macrophage population and greater concentrations of pro-inflammatory cytokines.…”
Section: Tablementioning
confidence: 99%
“…Dysregulated lipid turnover and abnormal fatty acid flux can act independently in contributing to the chronic pro-inflammatory profile of obesity. 72 Elements of the intracellular inflammatory signalling pathway are stimulated directly by raised intracellular concentrations of saturated fatty acids. Upstream along this pathway, abnormal circulating concentrations of saturated fatty acids also bind and activate immune pattern recognition receptors (toll-like receptors), for which bacterial lipopolysaccharide (LPS) is the usual ligand (see Herrera chapter).…”
Section: Lipid Turnovermentioning
confidence: 99%
“…30 This subpopulation is capable of metabolizing lipids released by necrotic adipocytes and initiating adaptive immune responses. 30 In our study using immunofluorescence we confirmed the presence of increased numbers of ATMs in all histologic subgroups compared with lean controls. We showed that the number of ATMs and crownlike structures did not differ between the histologic subgroups.…”
mentioning
confidence: 99%